Comparing non-alcoholic fatty liver disease indices in predicting the prevalence and incidence of metabolic syndrome in middle-aged adults - Byung Sik Kim; Hyun-Jin Kim; Seong Won Jeon; Kyung Hwan Kim; Dong Wook Kim; Jeong-Hun Shin (Heliyon)
Aims: This study aimed to compare the predictive power of the indices of non-alcoholic fatty liver disease (NAFLD), the fatty liver index (FLI), and the hepatic steatosis index (HSI) for the prevalence and incidence of metabolic syndrome (MetS) in a community-based prospective cohort over a 16-year follow-up period. Methods: Data from the Ansan–Ansung cohort of the Korean Genome and Epidemiology Study were used. We evaluated 8271 participants for MetS prevalence and 5242 participants without MetS at baseline for MetS incidence. Results: The baseline prevalence of MetS was 30.5 %. The FLI and HSI were significantly associated with MetS prevalence, with the FLI showing superior predictive ability compared with the HSI. During the 16-year follow-up period, 2286 participants (43.6 %) developed MetS. Both indices were significantly associated with the incidence of MetS. Time-dependent receiver operating characteristic curve analysis, Harrell's C-index, and integrated discrimination improvement indicated that the FLI demonstrated better predictive power for MetS incidence than the HSI. Conclusions: Given the increasing prevalence of MetS and its health implications, incorporating the FLI into clinical practice can improve early detection and intervention strategies. Future research should investigate the applicability of the FLI in diverse populations and its role in comprehensive MetS management protocols.